Keeping Encountered Information. - Marshall, Catherine C.; Jones, William (Communications of the ACM, 2006)
The article discusses implications that encountered information has for Personal Information Management (PIM) tools. A key challenge in the field of PIM is to decide about ways of keeping the encountered information. The number of ways to keep and manage information has increased considerably because of the overall increase in the number of devices, technologies and applications. The attendant fragmentation of personal information increases the chances of keeping something in the wrong place and forgetting it. Furthermore, encountered information may fall outside the usual assumptions underlying PIM technologies. Encountering unexpected, but potentially valuable, information may interrupt us rather than help us complete the current task. And we may not yet have the appropriate filing structure to store the encountered information. A good match between how something is kept and its envisioned role or function is essential for using the material effectively and enjoyably. PIM tool developers must remember that the utility, serendipity, and pleasure of re-encountering what ever is saved relies on the many ways used to interact with the information.